The Nature, Correlates, and Conditions of Parental Advocacy in Special Education. Issue 3 (2nd July 2016) - Burke, Meghan M.; Hodapp, Robert M.
ABSTRACT: Although parents often advocate for the best educational services for their children with disabilities, few studies examine parents' advocacy activities; identify parent-school relationship, parent, and student correlates of advocacy; or describe the conditions of advocacy. Responding to a national, web-based survey, 1087 parents of students with disabilities completed a 163-item questionnaire. A seven-item Special Education Rights and Advocacy Scale converged on a single factor. Higher levels of advocacy were found among parents who enacted their procedural safeguards, reported less satisfactory partnerships with schools, and were less satisfied with educational services. Parents engaging in the highest levels of advocacy described negative experiences, with schools refusing services, acting disingenuously, lacking trained personnel, and communicating poorly. Conversely (and with some exceptions), parents engaging in lesser amounts of advocacy reported positive experiences, were satisfied, and felt that their IEP teams were collaborative. High levels of parental advocacy may be a reaction to poor relationships with and behaviors by the school. Implications for researchers and practitioners are discussed.